Analisis E-Leadership Pada E-Government Pemerintah Daerah Demi Menyukseskan Transformasi New Normal di Era Pandemi Covid-19 - Yudha Herlambang Cahya Pratama (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The purpose of this study is to analyze e-leadership in the implementation of e-government by Indonesian regional government as an effort to succeed the transformation to the new normal. The research was carried out using qualitative approach with research data in the form of secondary data. The Data were then analyzed using qualitative analysis techniques consisting of four stages, namely data review, data reduction, data categorization, and data interpretation. The results of the study indicate that the e-government in regional governments still not implemented effectively and efficiently. This can be seen from the lack of integration in the application of e-government between government agencies, both at the central and regional levels. This situation also illustrates that e-leadership in the local government is still not optimal. Methods for optimizing e-leadership in e-government consist of: 1) Increasing e-leader knowledge of IT used in regional governments; 2) Creating a work culture that is conducive to the implementation of e-government; 3) Implement SPBE literacy promotion; 4) Development of PNS functional positions; 5) Implementation of partnerships with non-government parties to improve the technical competence of ASN related to e-government; 6) Using the EMAC approach to select e-leader candidates; and 7) Improving e-leadership capability in various decision-making domains. The optimization of e-leadership in the implementation of e-government by the regional government is expected to succeed the transformation into the new normal era through the dissemination of information to the public about the new normal concept and the importance of compliance with health protocols.